2017
DOI: 10.3390/nu9070674
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Mediterranean Dietary Pattern and Cognitive Health: A Systematic Review

Abstract: The ageing population is accompanied by increased rates of cognitive decline and dementia. Not only does cognitive decline have a profound impact on an individual’s health and quality of life, but also on that of their caregivers. The Mediterranean diet (MD) has been known to aid in reducing the risk of cardiovascular diseases, cancer and diabetes. It has been recently linked to better cognitive function in the elderly population. The purpose of this review was to compile evidence based data that examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(116 citation statements)
references
References 94 publications
5
102
0
4
Order By: Relevance
“…Previous studies have shown that cognitive performance was determined by both genetic and environmental factors [8][9][10][11][12][13][14][15]. For instance, fruits and vegetables [16], vitamin D [13], vitamin B, protein, folate [11,12] and polyphenols [17] have been proved to have protective effects on cognitive function, whereas some studies [14,15] indicated that high level of saturated fat and refined sugar were associated with impaired cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that cognitive performance was determined by both genetic and environmental factors [8][9][10][11][12][13][14][15]. For instance, fruits and vegetables [16], vitamin D [13], vitamin B, protein, folate [11,12] and polyphenols [17] have been proved to have protective effects on cognitive function, whereas some studies [14,15] indicated that high level of saturated fat and refined sugar were associated with impaired cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…The MedD has been already reported to exert beneficial effects on cardiovascular disease and additionally on cognitive performance mainly in healthy elderly individuals or individuals with increased cardiovascular risk 2,9,10 . The present results show an association between MedD and verbal memory in individuals with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The present results show an association between MedD and verbal memory in individuals with diabetes. Although the underlying mechanisms are currently unknown, one may speculate that the high content of antioxidants in MedD may contribute to better cognitive performance by reducing the production of reactive oxygen species and attenuating inflammatory processes, both of which have been linked to cognitive decline 10 . Furthermore, positive effects might be mediated by n-3 fatty acids (FA).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (52)(53)(54) demonstrate the association between the Mediterranean-style diet (MsD) and age-related neurodegenerative diseases especially Alzheimer's disease. According to the "Global Strategy on Diet, Physical Activity and Health", MsD can prevent many diseases including neurodegenerative diseases and improve the quality of life (55).…”
Section: Role Of Nutrition In Neurodegenerative Diseasesmentioning
confidence: 99%
“…MsD includes plenty of plant-based foods (such as fruits, vegetables, whole grains, legumes and nuts), a moderate to high intake of fish and sea food, a low to moderate intake of poultry, eggs, cheese and yogurt, low consumption of red meat, and a regular intake of red wine during the meals. A systemic review of the thirty-one population-based studies by (52) from Australia, China, France, Greece, Scotland, Spain, Sweden, and USA shows that MsD has the beneficial effects on cognitive function and reduces the risk of Alzheimer's disease and dementia. Similarly, another review of twenty-four observational-type studies (prospective and retrospective) by (54) from Australia, Canada, Finland, France, Japan, Norway and USA summarizes the impact of MsD on cognition and in Alzheimer's disease in human clinical trials.…”
Section: Role Of Nutrition In Neurodegenerative Diseasesmentioning
confidence: 99%